TECHNOLOGY OF UNIQUE BUILDINGS’ CONSTRUCTION IN THE CONSTRAINED CONDITIONS OF OPERATING ENTERPRISE - A. F. Andryushenkov; N. S. Volovnik; A. A. Andryushenkov (Вестник СибАДИ)
Introduction. There is a need for detailed consideration of technological solutions of the constructed object while the process of the work projects’ development (WPD). The features of WPD development are considered on the basis of the flare tower as a part of the flare installation of the oil refining enterprise. The problems of organizational and technological design (development of WPD) for such facilities’ type should be solved many times due to the fact that there is a modernization of oil refining enterprises in the country. Moreover, the obtained results of calculations allow conducting more rational technological solutions for the construction of the flare tower and such solutions affect the period of the flare installation.Materials and methods. The technology of the flare tower construction as a part of the flare installation is quite complex due to the features of the unique structure and cramped construction site. Accordingly, the choice of technology for the flare tower construction is made by using the features of its design solution and by the detailed consideration of options for installation mechanization. The options are evaluated by using an economic criterion (reduced cost). The calculations are based on modern installation cranes recommended for usage on this type of unique structures.Results. As a result of technical and economic calculations of the flare tower construction technology, the method of its construction is chosen due to the rational version of installation mechanization. The paper presents the calculations’ results of the given costs and the technical characteristics of the cranes. In addition, the technology of the flare tower installation is organized with the method of the tower blocks assembly.Discussion and conclusions. As could be seen, the construction technology by the mixed scheme on the chosen option is developed by the authors.